Preparation and electrochemical performance of activated carbon microspheres from recycled novolak phenol formaldehyde. (1st February 2021) - Guan, Mingjie; Li, Hui; Chen, Xianwen; Zhang, Shu
Graphical abstract: Schematic for the preparation procedure of NPF-ACMs. Highlights: We recycled novolak phenol formaldehyde resin into activated carbon microspheres. Optimal preparation process of microspheres were studied by the orthogonal method. The specific surface area of activated carbon microspheres is very high: 2528 m 2 /g. Activated carbon microspheres has good electrochemical properties as electrode. Abstract: In this study, an attempt is made to obtain porous activated carbon microspheres (ACMs) as supercapacitor electrodes by recycling waste novolak phenol formaldehyde (NPF) resins. These NPF-ACMs were prepared by a three-step procedure of hydrothermal synthesis, carbonization, and activation in turn. The effects of temperature, time, and sodium dodecyl sulfonate (SDS) addition on NPF-based microspheres were studied by the orthogonal method. The optimal preparation process of NPF-based microspheres was the following: 230 °C, 4 h, and a mass ratio of SDS: NPF of 24:1 by hydrothermal synthesis. Based on the above optimal conditions, NPF-ACMs were made, the yield of the microspheres after carbonization and chemical activation are 54% and 38%, and their electrochemical properties were analyzed. The NPF-ACMs had uniform size, a high surface area of 2528 m 2 g −1, good dispersion, a low impedance of 0.46 Ω, highest specific capacitance of 118.6 F g −1 at 0.5 A g −1, good rate capability with 79% retention from 0.1 to 10 A g −1 . Moreover, it showed high capacitance retention of 99.5% after 1000 cycles at a scan rate of 5 mV s −1 . The results showed that waste NPF can be used as promising ACMs of the electrode material to increase its utilization value.